Financial management - Kapil, Sheeba (Pearson, 2011)
Financial Management introduces students to the fundamental tools and concepts of corporate finance by explaining the reasoning behind various financial concepts. The book prepares students for life outside the classroom through snapshots from contemporary organizations, solved examples and application-based problems. The book includes short vignettes about the financial practices of organizations such as Steel Authority of India Limited, Hindalco Industries Limited, Amazon.com and Tata Motors; useful facts and rules of thumb, and provide insights into financial practices in organizations like Godrej Industries Ltd, Infosys Technologies Ltd and ICICI Bank; solved examples, solved problems and excel worksheets to help enhance students' understanding of numerical and MS Excel-based problems.